New opportunities in glioma therapy - awake craniotomy - Maria Golebiowska; Beata Golebiowska; Chonlada Siripanich; Maria Klatka; Malgorzata Wieleba (Kazimierz Wielki University, 2017)
In some populations over the past 30 years there has been an increase of 30% in brain tumors morbidity, in Poland, over two-fold increase within three decades. Even though the diagnostics is significantly increasing, the mortality still remains high - general statistics of survival is 34%, for the most malignant cases - less than 5%. Brain tumor resection is essential not only for the overall survival, but the post-operative quality of life is as important as the survival rate. Especially in motor and language area lesions, the greater resections with lesser post-operative complications are required. The modern opportunity in favour of such circumstances is tend to grow within awake craniotomy technique.   The aim of the study is to present the newest achievements in field of neurosurgical awake surgery. For the purpose of this study, most significant works have been reviewed in period 2000-2015.   Study reveals the growing importance of awake surgery with simultaneous necessity for new pre-operative technologies, which can support the greater outcomes of the surgeries. Apart from that, the concerns of the ethical matter can be withdrawn if the valid algorythms and guidelines are applied for this procedure.